Transcriptional Profiling at High Temporal Resolution Reveals Robust Immune/Inflammatory Responses during Rat Sciatic Nerve Recovery - Lingyan Xing; Qiong Cheng; Guangbin Zha; Sheng Yi (Hindawi Limited, 2017)
After peripheral nerve injury, immune/inflammatory responses are triggered, which are critical for nerve regeneration. Despite their importance, the underlying molecular changes in immune/inflammatory responses remain largely unknown. In this study, we systematically analyzed differentially expressed genes in immune/inflammatory-related pathways at high temporal resolution and experimentally validated gene expression changes with RT-PCR following sciatic nerve crush in rats. We found that immune/inflammatory reactions not only occur in the acute injury but also remained activated over two weeks after injury. Detailed bioinformatic studies suggested that multiple immune/inflammatory pathways, including agranulocyte adhesion and diapedesis, granulocyte adhesion and diapedesis, IL-6 signaling, and IL-10 signaling, were sustained activated during nerve degeneration and regeneration. Our current study expands our understanding of the molecular basis of altered immune/inflammatory-related pathways following injury and thus might offer the possibility of targeting related molecules as therapeutic intervention for peripheral nerve regeneration.